In Vitro Fermentability and Methane Production of Complete Feeds as Affected by Supplementation of Tree Leaves - Deuri, Pompi; Wadhwa, M. (Indian Journal of Animal Nutrition, 2018)
The study was taken up to assess the effect of supplementing tree leaves of Eucalyptus globules (safeda), Psidium guajava (guava) and Phoenix dactylifera (khajur) @ 1% on DM basis either individually or in combination on the in vitro fermentability and methane production potential of complete feed. Supplementation of diet with leaves of safeda, guava and khajur decreased net gas production (NGP) by 9.3, 7.6, 5.6%, respectively while the partition factor (PF) increased in comparison to unsupplemented diet. The supplementation of diet with tree leaves individually or in combination depressed the total and individual volatile fatty acids with mild increase in A: P ratio. The methane production was the lowest (P<0.05) when diet was supplemented with tree leaves of safeda, guava and khajur but was comparable with control diet. The increased fermentation efficiency by addition of leaves of safeda, guava and khajur showed decrease in methane production. On an average, the fermentative methane, H recovery, H consumption and VFA utilization index improved by 0.6, 9.6, 16.7 and 1.6%, respectively. It was concluded that the tree leaves supplemented at the rate of 1% each (DM basis) to complete feed seemd to have positive impact on in vitro fermentability and in depressing methane production. Further studies with higher levels of these tree leaves should be conducted as these might have potential in improving in vitro fermentability and mitigation of methane production.